Kajian Psikologis Humanistik Abraham Maslow: Hilangnya Motivasi Belajar Pada Remaja Akibat Kehilangan Orang Tua - Risydah Fadilah; Suci Permata Hati; Sofie Ahmira Rehgita Br Tarigan (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Background : Learning motivation is something that must be owned by every student. One of the factors that influence learning motivation is the fulfillment of basic needs. Objective : This study aims to determine the relationship between learning motivation in adolescents who have lost their parents based on Maslow's basic needs analysis. Methods : The research method used in writing this article is research with a qualitative approach. The model used in the research is a case study model with a junior high school student as the object of research. Collecting data in this study used observation and semi-structured interviews which were then analyzed using thematic analysis. Result : This study reveals that adolescents who have lost their parents experience grief and a bad state of trauma, there is no support as the main source of motivation and a loss of comfort. Analysis of the humanistic theory of the object in question shows that there is a significant relationship between the fulfillment of basic needs and the loss of learning motivation of students who have lost parents. Conslusion : In order to help students who have lost their parents recover their motivation to study, it is also important to involve the student's family and other resources such as a school counselor or psychologist.